Immunogenicity and protection conferred by an optimized purified inactivated Zika vaccine in mice. Issue 20 (6th May 2019) - Lecouturier, Valérie; Bernard, Marie-Clotilde; Berry, Catherine; Carayol, Sébastien; Richier, Eric; Boudet, Florence; Heinrichs, Jon
Highlights: An optimized, purified virus inactivated Zika vaccine (ZPIV-SP) was developed. ZPIV-SP elicited 100% seroconversion and protection from Zika virus in mouse models. ZPIV-SP displayed higher immunogenicity and efficacy than the first-generation vaccine. ZPIV-SP is suited for further evaluation in larger animal models and clinical studies. Abstract: After decades of inconsequential infections, and sporadic outbreaks in the Asia-Pacific region between 2007 and 2013, Zika virus caused a widespread epidemic in South America in 2015 that was complicated by severe congenital infections. After the WHO declared a Public Health Emergency of International Concern in February 2016, vaccine development efforts based on different platforms were initiated. Several candidates have since been evaluated in clinical phase I studies. Of these, a Zika purified inactivated vaccine (ZPIV), adjuvanted with aluminum hydroxide, developed by the Walter Reed Army Institute of Research (WRAIR), yielded high seroconversion rates. Sanofi Pasteur further optimized the vaccine in terms of production scale, purification conditions and regulatory compliance, using its experience in flavivirus vaccine development. Here we report that the resulting optimized vaccine (ZPIV-SP) elicited robust seroneutralizing antibody responses and provided complete protection from homologous Zika virus strain challenge in immunocompetent BALB/c mice. ZPIV-SP also showed improved immunogenicity compared with the first-generation vaccine, and improved efficacy in the more permissive interferon receptor-deficient A129 mice. Finally, analysis of the IgG response directed towards nonstructural protein 1 (NS1) suggests that viral NS1 was efficiently removed during the optimized purification process of ZPIV-SP. Together, these results suggest that the optimized vaccine is well suited for further evaluation in larger animal models and late-stage clinical studies.